Divergent optimal inflation rates in euro area countries or "does one size fit all"? - Caraballo, M. Ángeles; Efthimiadis, Tilemahos (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2014)
The aim of this paper is to derive the optimal inflation rate for the euro area (EA) countries from the relationship between the aggregate inflation and the Relative Price Variability (RPV). In order to achieve this goal, we have utilized monthly data for the Harmonized Index of Consumer Prices between January 1997 and June 2013 for the first twelve EA countries and for the EA aggregate. In the first stage, parametric and semiparametric estimations allow us to find that the inflation-RPV relationship shows a U-shaped functional profile for the majority of the countries. In the second stage, within this benchmark and using both kinds of estimations, we obtain the optimal inflation rate defined as the one that minimizes the RPV. Moreover, we test the sensitivity of our results to the time period and, for semiparametric estimation, to the bandwidth selected. For EA individual countries and for the EA aggregate, it is formally shown that although the European Central Bank’s “below but close to 2%” inflation target is (almost) optimal for the EA average, it is not close to the optimum inflation rate for most of the individual EA countries
Argumenta Oeconomica, 2014, Nr 1 (32), s. 15-40
Keywords: euro area; monetary policy; relative price variability; optimal inflation